FAKTOR-FAKTOR YANG MEMPENGARUHI INCOME SMOOTHING PADA INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014 – 2016 - Eviyanti Rosalie; Michelle Michelle; Henryanto Wijaya; Susanto Salim (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2019)
The purpose of this study is to empirically examine the influence of return on asset, debt to equity ratio, net profit margin and firm size towards income smoothing in consumer goods listed in Indonesia Stock Exchange from period 2014 – 2016. This study used 27 data from manufacture companies that have been selected using purposive sampling method with total 81 data for three years. The data used are secondary data in the form of financial statements. This research used Statistical Product and Service Solution (SPSS) version 19 software to process the data. The result of research shows that return on asset, net profit margin and firm size have no influence towards income smoothing. Debt to equity ratio has negative significant influence towards income smoothing.